ICMS personalizado e propostas de reforma tributária no Brasil: problemas e possibilidades - Lima, Andrew Souza de (2021)
This dissertation aims to identify an alternative to reduce socioeconomic deformities promot ed by consumption taxation, focusing on the onerosity of the Tax on Operations Relating to the Circulation of Goods and on the Provision of Interstate and Intermunicipal Transport and Communication Services - ICMS on taxpayers in fact, due to the existing normativity. It is known that the Brazilian tax burden is strongly impacted by taxes on consumption, and the ICMS, in this sense, stands out as the most relevant tax for the entities of the federation. Given the impact of the ICMS on market operations, it is identified that the tax regressiveness, a characteristic intrinsic to that, ends up placing a burden on taxpayers in fact. In this sense, the question that arises is whether there would be a way to reduce the socioeconomic deformities resulting from taxation on consumption, due to the norms of the ICMS according to the cur rent fiscal federalism. The deductive scientific method will be used, since the study will ad vance from the central aspects of ICMS taxation to its particularization, pointing out the dis tortions and envisioning reform measures. With regard to the approach, the exploratory and dialectical method will be adopted, as the theme presented must be analyzed considering the desires of the collectivity. With regard to the research technique, it will be bibliographic and elaborated from the reading, reproduction and systematization of the normativity and doctri nal and jurisprudential thoughts of the proposed theme, as well as the details of collection data obtained from the supervisory bodies. Based on the problem explained above, we propose as a hypothesis the personification of the ICMS to those who effectively bear the burden of its application, as well as analyzing what the tax reform proposals under discussion in Congress, PEC No. 45/2019 and PEC nº 110/2019, envision for the future of taxation on consumption. In this context, the possibility of adapting the reform measures to the intended solution is verified, without disregarding, however, the sanitary, social and economic chaos promoted by the COVID-19 pandemic.